2011
DOI: 10.1186/1745-6673-6-18
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of oxidative stress and its association with the urinary reducing capacity in bus maintenance workers

Abstract: BackgroundExposure to particles (PM) induces adverse health effects (cancer, cardiovascular and pulmonary diseases). A key-role in these adverse effects seems to be played by oxidative stress, which is an excess of reactive oxygen species relative to the amount of reducing species (including antioxidants), the first line of defense against reactive oxygen species. The aim of this study was to document the oxidative stress caused by exposure to respirable particles in vivo, and to test whether exposed workers p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 61 publications
(94 reference statements)
3
17
0
Order By: Relevance
“…This is in agreement with numerous previous reports studied in smokers 11,12) or bus depot workers, who were exposed to respirable particles and pollutants 27) ; however, our cross-sectional study can add new information by showing a significant association between the urinary 8-OHdG level and the CAVI as an indicator of arteriosclerosis in hypertensive patients. As CAVI has been demonstrated to be high in smoking subjects 24) , the smoking status also differed in the comparison between groups with normal and elevated CAVI in the present study (Table 4); therefore, we examined the relationship between urinary 8-OHdG and CAVI in 87 non-smokers in the present study.…”
Section: Association Between Cavi and Other Variablessupporting
confidence: 93%
“…This is in agreement with numerous previous reports studied in smokers 11,12) or bus depot workers, who were exposed to respirable particles and pollutants 27) ; however, our cross-sectional study can add new information by showing a significant association between the urinary 8-OHdG level and the CAVI as an indicator of arteriosclerosis in hypertensive patients. As CAVI has been demonstrated to be high in smoking subjects 24) , the smoking status also differed in the comparison between groups with normal and elevated CAVI in the present study (Table 4); therefore, we examined the relationship between urinary 8-OHdG and CAVI in 87 non-smokers in the present study.…”
Section: Association Between Cavi and Other Variablessupporting
confidence: 93%
“…For example, Sauvain et al (2011) found that oxidative stress levels in workers at a bus depot were elevated after a workday, compared to before work, and were more highly elevated at the end of a second consecutive workday than after the first workday. Relative to the general U.S. population, workers in the trucking industry most consistently exposed to higher levels of diesel exhaust (drivers and dock workers) had significantly elevated rates of both lung cancer and ischemic heart disease (Laden et al, 2007), while those with less exposure (hostlers and clerks) did not.…”
Section: Casac and Nrc Considerationsmentioning
confidence: 99%
“…Once produced, 8-OHdG is very stable and is not further metabolized in the systemic circulation. 19 Another advantage of this marker is that it is affected by neither diet nor cell turnover. 8 Due to these unique properties, 8-OH-dG is an ideal biomarker for determining the severity of DNA damage and oxidative stress.…”
Section: Commentmentioning
confidence: 99%
“…21 Sauvain et al and Wang et al suggested urinary 8-OH-dG as an oxidative stress indicator in kitchen workers of Chinese restaurants and bus maintenance workers, respectively. 19,22 Pan et al revealed that kitchen workers' urinary 8-OH-dG levels are higher than service staff. 23 In our study, we found that urinary creatinine adjusted 8-OH-dG levels are higher in TCE-exposed group compared with control group (p < .001).…”
Section: Commentmentioning
confidence: 99%